2009
DOI: 10.1038/ni.1721
|View full text |Cite
|
Sign up to set email alerts
|

Function of C/EBPδ in a regulatory circuit that discriminates between transient and persistent TLR4-induced signals

Abstract: The innate immune system is a two-edged sword; it is absolutely required for host defense against infection but, uncontrolled, can trigger a plethora of inflammatory diseases. Here we used systems biology approaches to predict and validate a gene regulatory network involving a dynamic interplay between the transcription factors NF-κB, C/EBPδ, and ATF3 that controls inflammatory responses. We mathematically modeled transcriptional regulation of Il6 and Cebpd genes and experimentally validated the prediction tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

19
309
2
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 252 publications
(333 citation statements)
references
References 37 publications
19
309
2
3
Order By: Relevance
“…C/EBPδ has been previously shown to be involved in the inflammatory response during persistent bacterial infection and has been suggested to act as an amplifier of the inflammatory response (7). Indeed, C/EBPδ −/− mice were able to resist a transient peritoneal infection with low-dose E. coli, but were highly susceptible to persistent peritoneal infection with high-dose E. coli.…”
Section: Discussionmentioning
confidence: 93%
“…C/EBPδ has been previously shown to be involved in the inflammatory response during persistent bacterial infection and has been suggested to act as an amplifier of the inflammatory response (7). Indeed, C/EBPδ −/− mice were able to resist a transient peritoneal infection with low-dose E. coli, but were highly susceptible to persistent peritoneal infection with high-dose E. coli.…”
Section: Discussionmentioning
confidence: 93%
“…Moreover, previous studies have shown that CEBP␦ was induced by proinflammatory signals, including TNF-␣ and IL-6, and that murine TLR4 stimulation leads to its activation in macrophages (23)(24)(25). We therefore determined whether activation of TLR8 signaling by R848 could lead to C/EBP␦ induction.…”
Section: R848 Enhances C/ebp␦ But Not C/ebp␤-mediated Induction Of Tlr8mentioning
confidence: 99%
“…Not surprisingly, ATF3-deficient macrophages produce elevated levels of IL-6 and IL12p40 cytokines in response to TLR 4 activator, a bacterial LPS (13,15). Mechanistically, the negative regulation of transcription by ATF3 may occur indirectly via inhibition of C/EBPd, a positive regulator of cytokine gene induction (16). In addition, recent studies have shown that ATF3 mediates epigenetic regulation of proinflammatory cytokines (13,17).…”
mentioning
confidence: 99%